Impact of a virtual learning environment on the conscious prescription of antibiotics among Colombian dentists (2022)
Appropriate antibiotic prescription contributes to reducing bacterial resistance; therefore, it is critical to provide training regarding this challenge. The objective of this study was to develop a virtual learning environment for antibiotic prescription and to determine its impact on dentists’ awareness, attitudes, and intention to practice. First, the learning content on multimedia resources was developed and distributed into three challenges that participants had to overcome. Then, a quasi-experimental study was performed in which the virtual learning environment was implemented on dentists from seven Colombian cities. The median of correct answers and the levels of awareness, attitudes, and intention to practice were compared before, immediately after, and 6-months post-intervention. Wilcoxon signed-rank and McNemar’s tests were used to determine the differences. A total of 206 participants who finished the virtual learning environment activities exhibited a favorable and statistically significant impact on the median of correct answers of awareness (p < 0.001), attitudes (p < 0.001), and intention to practice (p = 0.042). A significant increase occurred in the number of participants with a high level of awareness (p < 0.001) and a non-significant increase in participants with high levels of attitudes (p = 0.230) and intention to practice (p = 0.286). At 6 months, the positive effect on the median of correct answers on awareness and intention to practice persisted (p < 0.001); however, this was not evident for attitudes (p = 0.105). Moreover, there was a significant decrease in the number of participants who showed low levels of awareness (p = 0.019) and a slight increase in those with high levels of the same component (p = 0.161). The use of a virtual learning environment designed for dentists contributed to a rapid improvement in awareness and intention to practice antibiotic prescription; however, their attitudes and information retention need reinforcement.